DUKUNGAN KELUARGA TERHADAP PEMBERIAN KOLOSTRUM PADA IBU POSTPARTUM SECTIO CAESAREA - Dwi Astuti; Nasriyah Nasriyah; Atun Wigati (Jurnal Ilmu Keperawatan dan Kebidanan, 2024)
Background: The number of post sectio cesarea patients at PKU Aisyiyah Jepara Hospital in June 2021 – April 2022 was 458 patients, data on infants who were breastfed colustrum in postpartum mothers with cesarean sectio were 102 babies. It can be said that the coverage of colustrum breastfeeding at PKU Aisyiyah Jepara Hospital tends to be less than babies who are not given colustrum breastfeeding. While mothers who did not give colustrum breast milk as much as 22.2%. Objective: Knowing the relationship between family support for colostrum administration to postpartum SC mothers at PKU Aisyiyah Jepara Hospital. Method: A type of correlational analytic research with a cross sectional time approach. Large sample of 41 respondents with total sampling technique. The instrument used questionnaire. Analysis of statistical test data of Spearman Rho. Research Results: The majority of respondents' family support was sufficient, namely as many as 27 people (65.9%) and mothers gave colostrum as many as 32 people (78%). Conclusion: There is a relationship between family support for colostrum administration to   postpartum SC mothers at PKU Aisyiyah Jepara Hospital with p value 0.001 α 0.05 and r value = 0.487.